PENGEMBANGAN MEDIA SCRAPBOOK DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI PUBERTAS KELAS VI SEKOLAH DASAR - Wulan Putri; Wendri Wiratsiwi (ELENOR: Elementary School Journal, 2024)
Abstract. This research aims to develop digital scrapbook media for science subjects, puberty material, to improve the learning outcomes of sixth grade elementary school students who meet the criteria of valid, practical and effective. This type of research is research and development. The data collection instruments used in this research were expert validation sheets, teacher and student response questionnaire sheets, and question sheets.Based on the digital scrapbook media validation test, the average results obtained from the 3 validators were 85% (very valid), with the material expert validator 78%, the media expert validator 96.92% and the language expert validator 80%. And the teacher and student response questionnaire sheet as a test of practicality obtained teacher response questionnaire results of 85.71% (very practical) and student response questionnaire results of 92% (very practical). And the student test results as a test of effectiveness got a score of 90.9% (very effective). Based on this data, it shows that digital scrapbook media is valid, effective and practical.